PENGEMBANGAN MODUL PEMBELAJARAN BERBANTUAN GAME GENSHIN IMPACT UNTUK MENINGKATKAN KEMAMPUAN DAN MOTIVASI BELAJAR SISWA SMA N 1 TOMPASO PADA MATERI PELUANG - Lempas, Zefanya; Tilaar, Anetha L. F; Runtu, Patricia V. J. (LPPM Politeknik Saint Paul Sorong, 2024)
This research focuses on the development and implementation of a mathematics learning module based on the Genshin Impact game to improve high school students' learning ability and motivation on chance material. This research uses the Research and Development (R&D) method with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were 10th grade students at SMA Negeri 1 Tompaso. Data collection instruments included observation, interviews, and tests. This research makes a significant contribution to the development of innovative and interesting mathematics learning by utilising game technology. The developed learning module can be an alternative for teachers to create a fun and effective learning experience for students, especially on materials that are considered difficult such as opportunities. In addition, this research also opens opportunities for further research on the use of games in learning mathematics on other materials.